New Service Development in the Publicly Funded University: Overcoming Barriers and Developing Enablers - DREYER-GIBNEY, KATRIN (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
Today universities operate in an exceptionally difficult funding environment and in a context characterised by financial constraints, state imposed restrictions on critical strategic and operating issues and at the same time rising student numbers and a more diverse student population. A way to address these challenges is to engage in new service development (NSD). However, NSD requires NSD capabilities. In particular, in a mature and well established state funded university, existing NSD capabilities may not be sufficient to carry out the necessary changes to address the above challenges as they were developed in response to past and different policy priorities. NSD offers a multitude of research opportunities that consider the complex and diverse nature of service provision, for example service development within complex service systems, identifying drivers of sustained service innovation, and understanding the interrelationships among service product, service process and business model. NSD authors also propose that the field of service research needs to develop more contingency theories, reflecting for example contexts and individual differences. My research questions are: ?What barriers and enablers to new service development are evident in the publicly-funded university; and how might the barriers be overcome and the enablers be developed?? The research methodology I applied is that of insider action research. Over the period of two years and eight months I conducted seven NSD interventions in the setting of a mature, publicly funded university. Four interventions involved the development of commercial services and three involved non-commercial service development. In all, I was an actor engaged in service development. Whilst the research questions are derived from practice the thesis research contributes to existing knowledge in the following way: ? The study contributes to the contingency perspective of NSD, considering the range of service development types ? In developing a framework for managing NSD the study contributes to understanding ?what really happens in NSD?, highlighting NSD process dimensions and the emphases on them, activities of NSD actors and the sequence in which NSD dimensions are developed ? In this study I am applying the resource based view (RBV) to managing NSD in a publicly funded university and as such extending the understanding of the RBV in this domain ? The study contributes to an understanding of the resources and capabilities perspective of NSD by researching the distinctive relationship between operations resources and NSD My study contributes to the understanding of NSD not only in research terms but also in practical terms. It is of benefit to service operations practitioners who are tasked with NSD, in the publicly funded university and in other similar resource constrained environments. Over the course of the thesis research I developed an NSD framework for managing NSD that will help NSD managers to understand the informal and complex nature of NSD and how barriers and enablers to NSD might emerge. Further, the study provides insights how barriers could be overcome and enablers developed. The study proposes the application of Insider Action Research (IAR) as a tool for harnessing organisational learning and capability enhancements.
APPROVED
Keywords: Contingency Theory; Publicly Funded University; Operations Management; New Service Development; Action Research; Service Operations; NSD